2015
DOI: 10.1136/gutjnl-2015-310861
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors alter the composition of the gut microbiota

Abstract: ObjectiveProton pump inhibitors (PPIs) are drugs used to suppress gastric acid production and treat GI disorders such as peptic ulcers and gastro-oesophageal reflux. They have been considered low risk, have been widely adopted, and are often over-prescribed. Recent studies have identified an increased risk of enteric and other infections with their use. Small studies have identified possible associations between PPI use and GI microbiota, but this has yet to be carried out on a large population-based cohort.De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
616
5
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 710 publications
(689 citation statements)
references
References 46 publications
33
616
5
8
Order By: Relevance
“…One review of children up to 18 years of age reported that at least 23% of patients treated with histamine receptor 2 antagonists experienced side effects, as did 34% of those treated with proton pump inhibitors 32. Concerns have been raised with regard to the impact of proton pump inhibitors on the gut microbiome and the association between using proton pump inhibitors and small bowel bacterial overgrowth in children 33, 34. There is sparse evidence for the efficacy of other medication, such as pain relieving agents, prokinetic drugs or over‐the‐counter remedies such as simethicone for treating infantile colic 28, 35, 36, 37, 38.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
“…One review of children up to 18 years of age reported that at least 23% of patients treated with histamine receptor 2 antagonists experienced side effects, as did 34% of those treated with proton pump inhibitors 32. Concerns have been raised with regard to the impact of proton pump inhibitors on the gut microbiome and the association between using proton pump inhibitors and small bowel bacterial overgrowth in children 33, 34. There is sparse evidence for the efficacy of other medication, such as pain relieving agents, prokinetic drugs or over‐the‐counter remedies such as simethicone for treating infantile colic 28, 35, 36, 37, 38.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
“…5,17 Subsequent gut microbiota studies attributed the increased risk to unfavorable gut microbiota alterations caused by PPI use. [6][7][8] Human, animal and in vitro studies show an overlap between the specific gut microbiota alterations associated with PPI use (as found in Imhann et al Gut 2016) and the bacterial changes that lead to increased susceptibility to Clostridium difficile (as depicted in Fig. 2).…”
Section: Consequences Of Gut Microbiota Changes Caused By Medicationmentioning
confidence: 99%
“…Bacterial families associated with PPI use in 3 gut microbiota studies. [6][7][8] ; Consistent changes in 2 or all studies are marked in bold; NR D Not reported. Table 3.…”
Section: Other Commonly Used Drugs and The Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations